Comparative analysis of directional cue perception between vibrotactile and electrotactile using funneling illusion mapping methods - Junyeong Lee; Hosu Lee; Minkyung Kim; Yeongmi Kim; Jungwon Yoon (Scientific Reports)
Abstract Tactile illusion is a promising concept for navigation, sensory augmentation for assistance, virtual reality (VR), and mobile haptic interaction applications enabling efficient feedback with a limited number of actuators. Through the funneling illusion, directional cues can be generated using a tactor array-based system, transmitting cues even at locations where actuators are not physically mounted. This technique has been applied to various research objectives according to modality, mapping methods, body part, and other factors. Accordingly, experimental studies analyzing the perceptual characteristics of the funneling illusion mapping methods across different modalities are necessary. We examined the effectiveness of funneling illusion mapping methods using vibrotactile and electrotactile modalities on the trunk and shank. The study involved two types of experiments, circle tracking (continuous cue) and directional accuracy (discrete cue) experiments with 20 healthy participants. The experimental results showed that for the electrotactile modality, Power law-based mapping provided the most accurate and continuous cue on the shank for both cue types. Square and Power law-based mappings provided the most accurate and continuous cue on the trunk during the circle tracking experiment. For the vibrotactile modality, Linear mapping provided the most accurate and continuous cues during the circle tracking experiment. These results demonstrate that mapping method performance varies across experimental conditions. Our findings can guide the selection of experimental parameters when utilizing a tactor array-based system for the trunk and shank.